INOVASI MODEL PENGEMBANGAN BISNIS UMKM ERA DISRUPTION DENGAN BERTUMPU PADA MODAL MAYA - Bagis, Abdul Azis; Surasni; Santoso, Budi (Jurnal Abdi Insani, 2024)
The development of small and medium enterprises into sustainable business entities is a necessity, because the contribution of these entities is very significant to Indonesia's economic development. Building the sustainability of a business entity, in today's turbulent era, requires primary strength that comes from business actors, which reflects the power of virtual capital ownership. Based on empirical evidence so far, the ability of MSMEs to survive exceeds ten years, because the perpetrators utilize the power of virtual capital, including intellectual, social and trust capital. Proving a model for utilizing virtual capital for MSME players that is capable of providing business resilience beyond ten year operating period. Development and empowerment by introducing and utilizing virtual capital for MSME players, including intellectual capital, social capital and trust capital in a synergistic manner. The results of a study of small and medium enterprises in NTB confirm that the business actors who have post-Covid resilience are those who have succeeded in utilizing virtual capital, which includes intellectual capital, social capital and the credibility capital of the actors themselves, in a synergistic manner. Building the sustainability of creative small and medium businesses that have a long operating life (business longevity) needs to rely on the use of virtual capital.